136k views
4 votes
Y = x - 1

y = 2x + 2

When solving the system of equations (shown above) using substitution, the solution to the system is:

1. (3,2)

2. (4,3)

3. (-3,-4)

4.(-4,-3)

5. (2,-3)

6. (-3,2)

User Excray
by
4.9k points

2 Answers

10 votes

Answer:

(-4 -3) is the answer

Explanation:

x+3=0

x=-3

y=-4

User Andy Whitfield
by
5.0k points
7 votes

Answer: The correct answer is the third option, (-3,-4).

Step-by-step explanation: You plug in 2x + 2 for y, given that y = 2x + 2.

2x+2 = x - 1

x = -3

Now, you plug in -3 for x in an equation.

y = -3 - 1

y = -4.

(-3, -4)

User Fabilous
by
5.6k points